1986
DOI: 10.1002/jbmr.5650010407
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and metabolism of monomeric human calcitonin: Effects of age, sex, and thyroid damage

Abstract: Some data suggest that human calcitonin (CT) secretion is lower in women than in men, decreases with age and the menopause, and is absent in thyroidectomized persons. To further explore CT secretory physiology, we have studied basal and calcium-stimulated plasma immunoreactive CT (iCT) and silica-extractable monomeric CT concentrations in 148 healthy volunteers and 33 patients with a history of thyroid damage (total or subtotal thyroidectomy, radioiodine treatment for thyrotoxicosis). Both whole-plasma iCT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…Deftos and associates reported that in normal adult subjects, basal CT values were similar between men and women, but basal CT values decreased with age in both groups and the response to a calcium or pentagastrin challenge was less in women than in men [ 25 , 60 ]. A subsequent study by another group showed lower basal and stimulated CT values in women than in men, but no decrement in CT values with age [ 9 ]. The CT difference between women and men has been ascribed to a lower CT secretion rate in women [ 9 ].…”
Section: Calcitonin and Gender/agementioning
confidence: 99%
See 1 more Smart Citation
“…Deftos and associates reported that in normal adult subjects, basal CT values were similar between men and women, but basal CT values decreased with age in both groups and the response to a calcium or pentagastrin challenge was less in women than in men [ 25 , 60 ]. A subsequent study by another group showed lower basal and stimulated CT values in women than in men, but no decrement in CT values with age [ 9 ]. The CT difference between women and men has been ascribed to a lower CT secretion rate in women [ 9 ].…”
Section: Calcitonin and Gender/agementioning
confidence: 99%
“…However, no differences in bone mass has been shown when CT is absent in congenital hypothyroidism provided thyroid hormone is replaced [ 23 , 24 ]. Gender and age differences in CT have been shown with women having lower values than men and with decreasing CT values with age in some, but not all studies [ 9 , 25 ]. CT screening has been shown to be a useful tool for the diagnosis of medullary thyroid carcinoma [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…TALP and BALP were estimated on the day of collection as ALP has a half-life of 1 to 2 days (Swaminathan, 2001). Parathyroid hormone (PTH) was estimated using IRMA PTH kit (A11930, Beckman Coulter Company) and calcitonin was determined by DRG ELISA kit according to Tiegs et al (1986). Bone supernatants were used for estimation of malondialdehyde (MDA) according to Ohkawa et al (1979), glutathione peroxidase (GPx) according to Paglia and Valentine (1967), superoxide dismutase (SOD) according to Nishikimi et al (1972) and total antioxidant capacity (TAC) according to Koracevic et al (2001).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…In the only 2 patients (1 male, 1 female) should the mild CT increase above 10 pg/ml observed also be considered as normal based on the finding of such values in healthy subjects and particularly in men, in which CT is reported to be higher than in women [16,17,18]. We thus demonstrate through a large series of patients that chronic pHPT-related hypercalcemia does not induce hypercalcitoninemia.…”
Section: Discussionmentioning
confidence: 61%
“…The finding of an increased CT value needs to suspect MTC, mainly for basal CT values above 100 pg/ml, whereas either CCH, or microscopic MTC or other pathological conditions may induce mild hypercalcitoninemia [16,17,18]. When pHPT is associated to MTC, MEN2A may be strongly suspected.…”
Section: Discussionmentioning
confidence: 99%